Application of Deep Breath Relaxation Technique to Lower Headache in Hypertension Patients - Nonik Aprilliya; Rahayu Winarti (Proceedings of the International Conference on Nursing and Health Sciences, 2020)
Hypertension is a persistent blood pressure with systolic pressure above 140 mmHg and diastolic blood pressure above 90 mmHg. Hypertension includes diseases with a fairly high incidence rate. Hypertension in Indonesia itself is a condition often found in primary health services with a high prevalence, which is 31.7%. Non-pharmacological management to lower the scale of hypertensive headaches, one of which uses deep breath relaxation techniques. The purpose of this research is to find out. Application of deep breath relaxation techniques to lower the scale of headache in hypertensive patients in jakenan area. This research uses pre-experimental designs with a one-group pretest-posttest design research, with 2 respondents in Jakenan Region. Based on the results showed after the patient performed routine deep breath relaxation techniques obtained a decrease in the pre-post test scale of headache in hypertension patients. There is an influence of deep breath relaxation techniques to lower the scale of headache in hypertensive patients in jakenan region.